Synthesis of 8-Oxabicyclo[3.2.1]octanes by TiCl4-Mediated Reactions of 3-Alkoxycyclobutanones and Allenylsilanes - Onnagawa, Tatsuo; Yamazaki, Mizuki; Yoshimura, Tomoyuki; Matsuo, Jun-ichi (Synlett, 2018)
1-Substituted allenylsilanes reacted with 3-alkoxycyclobutanones in the presence of TiCl4 to afford 8-oxabicyclo[3.2.1]octan-3-ones stereoselectively. Nucleophilic attack of allenylsilanes to a 1,4-zwitterionic intermediate formed from 3-alkoxycyclobutanones and TiCl4 followed by 1,2-silyl migration, five-membered cyclization with an alkoxy group, and seven-membered cyclization of titanium enolate was proposed. Deuteration and one-pot Peterson olefination suggested that alkyl titanium species were formed after cyclization to 8-oxabicyclo[3.2.1]octane skeletons.
Keywords: cyclobutanone; allenylsilane; Lewis acid; 8-oxabicyclo[3.2.1]octane; alkyl titanium bond